Pharmacokinetic Comparison of Omeprazole Granule and Suspension Forms in Children: A Randomized, Parallel Pilot Trial - Karami, S.; Dehghanzadeh, G.; Haghighat, M.; Mirzaei, R.; Rahimi, H. R. (Drug Research, 2016)
Although, omeprazole is widely used for treatment of gastric acid-mediated disorders. However, its pharmacokinetic and chemical instability does not allow simple aqueous dosage form formulation synthesis for therapy of, especially child, these patients. The aim of this study was at first preparation of suspension dosage form omeprazole and second to compare the blood levels of 2 oral formulations/dosage forms of suspension & granule by high performance liquid chromatography (HPLC). The omeprazole suspension was prepared; in this regard omeprazole powder was added to 8.4% sodium bicarbonate to make final concentration 2 mg/ml omeprazole. After that a randomized, parallel pilot trial study was performed in 34 pediatric patients with acid peptic disorder who considered usage omeprazole. Selected patients were received suspension and granule, respectively. After oral administration, blood samples were collected and analyzed for omeprazole levels using validated HPLC method. The mean omeprazole blood concentration before usage the next dose, (trough level) were 0.12±0.08 µg/ml and 0.18±0.15 µg/ml for granule and suspension groups, respectively and mean blood level after dosing (C2 peak level) were 0.68±0.61 µg/ml and 0.86±0.76 µg/ml for granule and suspension groups, respectively. No significant changes were observed in comparison 2 dosage forms 2 h before (P=0.52) and after (P=0.56) the last dose. These results demonstrate that omeprazole suspension is a suitable substitute for granule in pediatrics.
Keywords: istability; aqueous dosage form; high performance liquid chromatography; pilot trial study